Die größte Minderheit in Europa und die Problematik ihrer Ausbildung im tschechischen Schulsystem. Soziokulturelle Hintergründe des schulischen Misserfolges von Roma-Kindern und Jugendlichen - Procházka, Miroslav; Jílková, Hana (Wydawnictwo Naukowe UAM, 2012)
The text is focused on the social and cultural determinants of the school failure of Romani children and young adults in Czech Republic. The complicated educational situation, as well as integration difficulties of Romani students was analyzed both internally and externally, including e.g. the European Union’s recommendations concerning the national Roma integration strategies. The challenges faced by Romani students in the classroom of a ‘mainstream’ school system were addressed from the perspective of everyday school practice. Special attention was put on views and experiences of teachers with the inclusive Roma education in Czech Republic.
The biggest minority in Europe and the problems of its education in the Czech school system. Social and cultural background of the school failure of Roma children and youth
Keywords: Romani students; Czech Republic; Roma integration strategy; education for Roma children in European Union; teacher training in Roma education